2014
DOI: 10.4238/2014.march.17.8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the bone morphogenetic protein 15 gene and their effect on sperm quality traits in Chinese Holstein bulls

Abstract: ABSTRACT. Bone morphogenetic protein 15 (BMP-15) expression has been detected in the testis, but its roles in this organ has not been well elucidated. We evaluated polymorphisms of the BMP-15 gene by PCR-SSCP and PCR-RFLP in 212 Chinese Holstein bulls, and investigated possible associations with sperm quality traits, including semen volume per ejaculate, sperm density, fresh sperm motility, thawed sperm motility, acrosome integrity rate, and abnormal sperm rate. A single nucleotide polymorphism (C5697T) in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Mutations of the GDF9 gene have an effect on sperm quality traits . In bulls, a single‐nucleotide polymorphism of the BMP15 gene has a significant effect on fresh sperm motility . It was concluded that BMP15 should be considered as a potential genetic marker for sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the GDF9 gene have an effect on sperm quality traits . In bulls, a single‐nucleotide polymorphism of the BMP15 gene has a significant effect on fresh sperm motility . It was concluded that BMP15 should be considered as a potential genetic marker for sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…bmp15l is expressed in the salmon testis/germ cells, as well as in the testis of several species (Clelland et al, 2006;Chen et al, 2012;Zhang et al, 2014;Vilchez et al, 2015). Interestingly, an association between mutation in the BMP15 gene and sperm quality was recently reported for Chinese Holstein bull, and the authors of this study suggest that BMP15 may regulate testicular function, given its high expression in the bull testis (Sun et al, 2014). Here, we showed that bmp15l expression is restricted to the germ cells of the salmon testis, where it may also regulate sperm quality.…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 99%
“…Differences in the pregnancy rates related to polymorphisms of the BMP15 gene have been reported by Sun et al [30], who found that Chinese Holstein bulls of the CT genotype had a significantly lower sperm motility than did bulls of the CC or TT genotypes. In sheep, Chen et al [13] reported the expression of BMP15 in the epididymis of rams, which was significantly higher in a less-fecund breed (Sunite) than it was in a high-fecundity breed (Small Tail Han).…”
Section: Discussionmentioning
confidence: 59%